Endovascular Treatment of Acute Lower Limb Ischemia Associated with Cocaine Use: A Scoping Review (2024)
ABSTRACT: The endovascular treatment of acute lower limb ischemia associated with cocaine use is an underexplored topic. This scoping review aims to map existing information and point out potential knowledge gaps for future research. We searched databases with a strategy of terms and keywords (Cocaine, Acute, Lower Limb, and Ischemia) for articles related to acute ischemia in the lower limbs and cocaine use. We established eligibility and exclusion criteria and searched without restrictions on language or date of publication. We obtained five case reports published between 2004 and 2015. Most of the patients were men with an average age of 38 years. Treatments were heterogeneous. Most patients showed improvement after surgical thrombectomy. The sample size and variety of interventions limit the generalizability of the results, so it is necessary to do more studies with robust methodologies to standardize treatments and improve the understanding of the condition.